Listening to young lives at work in Vietnam: second call - Porter, C; Favara, M; Hittmeyer, A; Scott, D; Le Thuc, D (Young Lives, 2020)
This brief report provides headline findings from the second of the three calls in Young Lives at Work's COVID-19 Phone Survey in Vietnam